Assessing And Understanding The Current Situation In Information Systems - Maghfiroh, Anisatul (Journal of Renewable Engineering, 2024)
This study aims to examine the information system strategy in supporting the alignment between business needs and technology utilization through the Business Process Reengineering (BPR) approach. In a dynamic business environment, understanding external opportunities and threats, as well as the organization's internal capabilities, is an important foundation in designing information systems that can drive efficiency, effectiveness, and competitive advantage. Information systems not only play a role as operational support, but also as a driver of strategic transformation through innovation in processes, structures, and organizational culture. This study uses a qualitative descriptive method with a case study approach, involving in-depth interviews, observations, and documentation studies. The analysis techniques used include Critical Success Factors (CSF), Balanced Scorecard (BSC), and gap analysis to map actual conditions and determine future strategies. The results of the study are expected to produce an application portfolio that is in accordance with the needs of the organization, as well as a BPR strategy that is oriented towards improving service quality, reducing costs, and customer satisfaction. The strategic value of information systems is largely determined by the extent to which business understanding is integrated into the design of an adaptive system. Active participation at all levels of the organization, including through workshops based on actual data, is key to formulating effective and sustainable strategies.